Discovering Fatimah's Kampung: Author's Creative Process (KEMANUSIAAN The Asian Journal of Humanities, 2009)
The author of Fatimah's Kampung, Iain Buchanan, is an independent writer/illustrator. Below is an account of the author's creative process.